О применении реконфигурируемых вычислителей для решения вопросов защиты информации, пересылаемой в грид-среде - Гильгурт, С.Я.; Пухова, Г.Е.; Гиранова, А.К.; Пухова, Г.Е. (Моделювання та інформаційні технології, 2009)
The application of RUCs (FPGA-based Reconfigurable Unificated Coprocessors) to solve the information security tasks in the Grid-computing is investigated.